A Novel Wideband Common-Mode Noise Suppression Filter That Combines Mushroom and Defected Corrugated Reference Plane Structures - Chung-Ke Yu; Ding-Bing Lin; Hsin-Piao Lin (Applied Sciences, 2023)
A novel wideband common-mode (CM) suppression filter is proposed for high-speed transmission. The filter is embedded in 3 10 mm × 10 mm layers of a printed circuit board (PCB) that combines a mushroom structure and a defected corrugated reference plane structure (MDCRP). Using the novel MDCRP structure generates more resonance frequencies in the CM current return path. This generates a wider CM noise suppression performance. We used a simulation method to obtain the best geometric parameters for the MDCRP structure. The experimental results proved that the full-wave simulation results were consistent with the actual measurement results. This novel filter shows good signal integrity according to actual measurements, and the insertion loss can be kept to less than −2.306 dB from DC to 21 GHz in differential mode (DM). The CM noise can be suppressed by over −10 dB from 5.09 GHz to 20.62 GHz. The fractional bandwidth is 120.8%, and the CM noise improves by 64.5%. An eye diagram proves that the filter can support a 20 Gb/s transmission rate with complete differential signal transmission capability. The MDCRP structure filter can support HDMI 2.0, PCI Express 4.0, USB 3.2, and SATA Express. Therefore, the filter meets current computer and server system products’ design needs.